Anti‐Jo1 autoantibodies, from clinic to the bench. Issue 2 (31st March 2022) - Galindo‐Feria, Angeles S.; Horuluoglu, Begum; Lundberg, Ingrid E.
Abstract: Introduction: Idiopathic inflammatory myopathies (IIM) also known as myositis, is a chronic autoimmune disease which affects muscles, skin, joints and lung. One of the most common autoantibodies with a prevalence of 25‐35%, is the anti‐Jo‐1 autoantibodies, targeting the histidyl‐transfer RNA synthetase (HisRS). These autoantibodies are strongly associated with a distinct clinical phenotype called anti‐synthetase syndrome (ASyS) that includes interstitial lung disease (ILD), myositis, arthritis and Raynaud's phenomenon. The mechanism of how autoantibodies are produced and how they contribute to disease pathogenesis is unclear. Areas Covered: In this review we will discuss the clinical manifestations associated with Jo‐1 autoantibodies, and the association with clinical features. Moreover, we will also review the molecular characteristics of the antibodies and how they affect the cells of the immune system in order to understand possible disease mechanisms. Abstract : Clinical manifestations and cellular/molecular pathogenesis of Jo1 + IIM Key points: Clinical manifestations associated with the presence of anti‐Jo1 autoantibodies and how the levels of autoantibodies correlate with disease activity. Molecular characteristics of autoantibodies and their effects on immune cells to understand the contribution of autoantibodies and autoantigen to disease pathogenesis.